Diversidade de Candida spp. na cavidade oral em pacientes com Câncer de Cabeça e Pescoço em tratamento radioterápico - Izabella Nobre Queiroz (2021)
The objective of this study was to evaluate the diversity and prevalence of Candida sp. in the oral cavity of patients with head and neck cancer during radiotherapy treatment. The study was carried out with two groups. The control group included individuals with no history of cancer and the case group of individuals with head and neck cancer undergoing radiotherapy treatment at the Hospital da Baleia in Belo Horizonte, Minas Gerais. In both groups, samples from the oropharyngeal region were collected. In the control group, only one sample was used and in the case group, two collections were carried out: before the beginning of radiotherapy and between the 15th and 20th radiotherapy fraction. Isolation and presumptive identification were performed on plates containing CHROMagarCandida® and the final identification was with the MALDI-TOF-MS technique. There were 70 individuals in the case group and 160 in the control group. In the control group, 41 individuals showed at least one colony of Candida sp. On the culture plates, with 47 isolates and eight different Candida spp. species. In the case group, 33 individuals had at least one colony of Candida sp. on the culture plates, with 56 isolates and thirteen different Candida spp. species. In the 1st case group collection, there were 29 isolates and ten different types of Candida spp. species. In the 2nd case group collection, there were 27 isolates and nine types of different Candida spp. species. In both groups the predominant species was C. albicans. The control group had 57.45% C. albicans and 42.56% non-albicans species and the case group 46.42% C. albicans and 53.59% non-albicans species. Fungi other than Candida sp. were also identified in the case group. There was greater isolation of Candida sp. during radiotherapy (p <0.05) than that in the controlo group. The study found that C. albicans is the specie more prevalent in non-oncological and oncological individuals, that patients with head and neck cancer have greater diversity of Candida spp. and that during radiotherapy it is easier to isolate Candida spp. species.